Impact of a Dedicated Outpatient Parenteral Antibiotic Therapy Clinic on Patient Outcomes - Ibaraki, Makoto (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.